(untitled) (Global Journal of Human-Social Science, 2012)
Leonard Bloomfield is accused of neglecting the meaning of Language and focusing on its structural aspect only The present paper is an attempt to clarify Bloomfield s understanding of linguistics This is done by means of studying his views of structuralism and linguistics